Plectranthus scutellarioides (L.) Reduces the Rectal Temperature of Diphteria-Pertussis-Tetanus Vaccine-Induced Mice - Yudha Prabowo; Nyi M. Saptarini; Sri A. Sumiwi; Jutti Levita; Imam A. Wicaksono; Moelyono Moektiwardoyo (Universitas Padjadjaran, Indonesia)
The pharmacological activities of Plecranthus sp include anti-oxidant, antimicrobial, inhibition on cyclooxygenase (COX) and xanthine oxidase, and cytotoxic activity. The aim of this work was to study the antipyretic activity of P. scutellarioides (L.) extract on animal model. Twenty seven Swiss Webster male mice were divided into nine groups and were pyrexia-induced by using 0.1 ml of diphteria-pertussis-tetanus (DPT) vaccine. Their body temperature was measured every 60 minutes. After 4 hours of DPT vaccine injection, the mice were treated with (I) Arabic gum suspension (PGA) 2%; (II) paracetamol 16.25 mg/kg BW; (III) paracetamol 32.5 mg/kg BW; (IV) paracetamol 65 mg/kg BW; (V) paracetamol 130 mg/kg BW; (VI) P. scutellarioides extract 70 mg/kg BW; (VII) P. scutellarioides extract 140 mg/kg BW; (VIII) P. scutellarioides extract 280 mg/kg BW; (IX) P. scutellarioides extract 560 mg/kg BW. Data were analyzed using SPSS 21. Result showed that the body temperature of the mice started to rise at 2.5 hours and reached its peak at 4 hours after vaccine induction. The P. scutellarioides extract dose 280 mg/kg of BW indicated an 80.47% decrease (α= 0.05) compared to paracetamol dose 130 mg/kg of BW which decreases 85.43% of the animals’ fever. Interestingly, higher dose of the extract indicated a decrease in the antipyretic effect. We concluded that P. scutellarioides might possess antipyretic activity which started as early as 5 hours post vaccine-induced and was maintained for 3 hours. This plant needs further scientific exploration Keywords: Diphteria-pertusis-tetanus vaccine, anti-pyretic, rectal temperature, Webster mice